Os paradigmas no direito e suas anomalias: hermenêutica dialética e o justo atual segundo uma consciência paradigmática - Danilo Ribeiro Peixoto (2019)
A view that seeks contemporary meanings of Justice implies seeing it as a matter given internally to History from a conditioned rationality that is conscious of its own precariousness. Their judgements are formed from an understanding activity that is simultaneously made possible and limited by a historical horizon. A conception of Justice is formed through experience and depicts a Will that negates experience itself, as experimented by Consciousness. Despite the common pretension to see reality as only objectivity, subjectivity Is always inherent to constitution of meanings, especially in practical reasons sphere. Law is seen today in a context which the Constitution and Constitutional Law integrate the core of juridical systems and juridical debates. It is relevant nowadays a perspective that sees Law from a paradigmactical rationality, which has influence to actual juridical meanings. The concept of paradigm is treated rather differently in Law Theory and Philosophy of Law comparatively to its original context, in Thomas Kuhns The Structure of Scientific Revolutions; although it is possible to understand some of its original concepts as analogies. One of these concepts is the anomaly, which could be seen in Law as inspired by Kuhns theory, but would need to acquire specific juridical treatment. From a hermeneutical and dialectical perspective, it is understood that the idea of paradigm in Law must recognize the precedence of a historical horizon, that allow the possibilities of understanding, and it also needs a fundament in an ethical-juridical tradition. Furthermore, paradigm must be seen in parallel with its insufficiencies and specific negations. The concept of anomaly in Law contemplates specific notions of a paradigmatic negation, also permitting possibilities of paradigm enhancement through negation. A paradigmatic reconstruction based in Law as a specific juridical order, associated with the awareness of its anomalies is capable to retrieve a path to conceive actual meanings of Justice. This way, it could also qualitatively affect judicial application and contribute to Justice effectiveness. The awareness of anomalies, then, is seen as a requisite to paradigm improvement and a viable requisite to actual Justice effectiveness from a paradigmatic perspective. It could also represent a first step towards a better materialization of the actual Will that Law manifests in the present.